Corruption crimes’ forensic prevention in the sphere of housing and public utilities - Andrey Vladimirovich Borbat, Gyunay Aladdinovna Alieva, Ekaterina Nikolaevna Arestova; Elena Anatolevna Mironova, Tatyana Nikolaevna Sinyukova, Igor Alekseevich Burmistrov, Larisa Mikhailovna Zeynalova (Opción, 2019)
This article is aimed to comprehensive analysis of the issues of preventive nature arising in the investigation practice of corruption crimes in the housing and communal services sector. Statistical, comparative-legal and sociological methods are used to identify the existing problems in the Russian Federation for suppressing corruption-related crimes. As a Conclusion, the authors suggest to create specialized investigative units at the investigation departments at the regional levels throughout the country, aimed directly at investigating crimes in the sphere of housing and public utilities including corruption. The materials of the article can be useful both for law enforcers and for students.